The Impact of Green Finance on Clean Power Generation: Evidence Based on China - Yan , Ziwei; Cui , Chunying; Liao , Chenjia (Strategic Planning for Energy and the Environment, 2023)
In order to test whether green finance at the provincial level can promote clean power generation (CPG) to promote clean power energy, this paper, based on the China provincial panel data from 2003 to 2018 and takes a sample of 30 provinces. The study finds that the credit supply in green finance can effectively promote CPG proportion. Furthermore, the promotion effect of CPG is more indeterminate in the provinces with large power output, while those with large power input are relatively small. This paper explains the above conclusions from the perspective of primary energy production and CPG structure: (1) Main new power generation capacity is clean energy in the huge energy consumption provinces, the effect of green finance is outstanding; (2) In provinces with the large coal-burning production, which are restricted by the industrial structure and energy structure, the effect of green finance on promoting CPG is not apparent, and the energy saving and emission reduction of traditional thermal power units are still the main focus.